(untitled) (Global Journal of Medical Research, 2023)
Background Nigeria ranks within the top eleven countries of the world with the least average life expectancy from birth As a result the middle-elderly population is fast eroding The worse hit in this scenario is the palliative care of the elderly who is neglected due to poor social determinants of health occasioned by leadership failure Multiple myeloma is a common haematological malignancy in the middle-elderly target population that requires palliative care Unfortunately the quality of palliative care of people living with multiple myeloma in Nigeria is low partly due to grossly inadequate annual health budget Aim To improve the quality of palliative care of multiple myeloma in Nigeria using actionable quality improvement frameworks